Robert E. Wilson papers - Wilson, Robert E. (Robert Erastus), 1893-1964.
Correspondence, speeches, reports, articles, congressional testimony, clippings, printed matter, subject files, clippings, printed matter, and other papers relating primarily to Wilson's career with Standard Oil Company (Indiana), the petroleum industry in general, atomic energy, and the U.S. Atomic Energy Commission. Correspondents include K.T. Compton, Ralph K. Davies, Chet Holifield, and Ernest B. Tremmel.
Chemical engineer, businessman, and public official.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Compton, K. T. -- 1887-1954 -- Correspondence; Davies, Ralph K. -- 1897-1971 -- Correspondence; Holifield, Chet, -- 1903- -- Correspondence; Tremmel, Ernest B., -- 1916- -- Correspondence; U.S. Atomic Energy Commission; Standard Oil Company (Indiana); Petroleum industry and trade; Petroleum industry and trade -- Indiana; Nuclear energy; Businessmen; Chemical engineers; Public officials